IFT proteins spatially control the geometry of cleavage furrow ingression and lumen positioning. Issue 1 (December 2017) - Taulet, Nicolas; Vitre, Benjamin; Anguille, Christelle; Douanier, Audrey; Rocancourt, Murielle; Taschner, Michael; Lorentzen, Esben; Echard, Arnaud; Delaval, Benedicte
Abstract Cytokinesis mediates the physical separation of dividing cells and, in 3D epithelia, provides a spatial landmark for lumen formation. Here, we unravel an unexpected role in cytokinesis for proteins of the intraflagellar transport (IFT) machinery, initially characterized for their ciliary role and their link to polycystic kidney disease. Using 2D and 3D cultures of renal cells, we show that IFT proteins are required to correctly shape the central spindle, to control symmetric cleavage furrow ingression and to ensure central lumen positioning. Mechanistically, IFT88 directly interacts with the kinesin MKLP2 and is essential for the correct relocalization of the Aurora B/MKLP2 complex to the central spindle. IFT88 is thus required for proper centralspindlin distribution and central spindle microtubule organization. Overall, this work unravels a novel non-ciliary mechanism for IFT proteins at the central spindle, which could contribute to kidney cyst formation by affecting lumen positioning. Cytokinesis relies on central spindle organization and provides a spatial landmark for lumen formation. Here, the authors show that intraflagellar transport proteins are required for the localization of the cytokinetic regulator Aurora B and subsequent cleavage furrow ingression and lumen positioning.